2015
DOI: 10.1590/s1415-475738120140087
|View full text |Cite
|
Sign up to set email alerts
|

Novel splice-affecting variants in CYP27A1 gene in two Chilean patients with Cerebrotendinous Xanthomatosis

Abstract: Cerebrotendinous Xanthomatosis (CTX), a rare lipid storage disorder, is caused by recessive loss-of-function mutations of the 27-sterol hydroxylase (CYP27A1), producing an alteration of the synthesis of bile acids, with an accumulation of cholestanol. Clinical characteristics include juvenile cataracts, diarrhea, tendon xanthomas, cognitive impairment and other neurological manifestations. Early diagnosis is critical, because treatment with chenodeoxycholic acid may prevent neurological damage. We studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
6
0
2
Order By: Relevance
“…At 42 y: severe spastic tetraparesis, flexum of the 4 limbs, severe dysphagia. 64 Involutive cerebellar and frontal regions, bulbar and CWML NA NA NA p.Val86Glufs30Ter / p.Arg395Cys [ 21 ] 26 M Japan 65 77 + + + NA 13 (10.4 μg/mL) Normal Cervical dorsal column hyperintensities CDCA 750 mg NA p.Gln85Arg / p.Arg405Gln [ 22 ] 27 F NA 5 52 NA + + NA Seizures, development delay, dystonia, ataxia, dysarthria, dysphagia, wheelchair at 30y., bedridden at 49 y. 19.6 Cerebral and CWML and atrophy, extensive, symmetric supra and infra-tentorial hyperintensities Central and posterior SCWM, C7 through thoracic vertebra NA NA Confirmed by genetic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 42 y: severe spastic tetraparesis, flexum of the 4 limbs, severe dysphagia. 64 Involutive cerebellar and frontal regions, bulbar and CWML NA NA NA p.Val86Glufs30Ter / p.Arg395Cys [ 21 ] 26 M Japan 65 77 + + + NA 13 (10.4 μg/mL) Normal Cervical dorsal column hyperintensities CDCA 750 mg NA p.Gln85Arg / p.Arg405Gln [ 22 ] 27 F NA 5 52 NA + + NA Seizures, development delay, dystonia, ataxia, dysarthria, dysphagia, wheelchair at 30y., bedridden at 49 y. 19.6 Cerebral and CWML and atrophy, extensive, symmetric supra and infra-tentorial hyperintensities Central and posterior SCWM, C7 through thoracic vertebra NA NA Confirmed by genetic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The p.Arg395Cys substitution affects a highly conserved sequence of the adrenodoxin binding site and was shown to strongly reduce CYP27A1 enzyme activity [ 51 ]. Tridimensional protein modelling showed that Arg395 is located within the ERR triad (the glutamine-arginine-arginine motif conserved in all cytochrome P450 sequence) and its substitution to cysteine was suggested to favour misfolding and possibly affects adrenodoxin binding [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tridimensional protein modeling showed that Arg395 is located within the ERR triad (the glutamine-arginine-arginine motif conserved in all cytochrome P450 sequence) and its substitution to cysteine was suggested to favour misfolding and possibly affects adrenodoxin binding [23].…”
Section: Discussionmentioning
confidence: 99%
“…Es interesante destacar que esta variante tiene una alta prevalencia en España 16 . Otros reportes de CXT en Chile reflejan la variabilidad clínica de esta enfermedad: un caso con presentación típica asociado a xantomas tendíneos 18 , otro asociado a macrocefalia y dismorfias faciales, y otro sin xantomas tendíneos visibles 19 .…”
Section: Discussionunclassified